Web-based follow-up tool (ePIPARI) of preterm infants-study protocol for feasibility and performance - Saarinen Tiina; Ylijoki Milla; Lehtonen Liisa; Munck Petriina; Stolt Suvi; Lapinleimu Helena; Rautava Päivi; Haataja Leena; Setänen Sirkku; Leppänen Marika; Huhtala Mira; Saarinen Katriina; et al. (BMC, 2025)
Background Preterm infants have a risk of health and developmental problems emerging after discharge. This indicates the need for a comprehensive follow-up to enable early identification of these problems. In this paper, we introduce a follow-up tool "ePIPARI - web-based follow-up for preterm infants". Our future aim is to investigate whether ePIPARI is a feasible tool in the follow-up of preterm infants and whether it can identify children and parents in need of clinical interventions.
Methods ePIPARI includes eight assessment points (at term age and at 1, 2, 4, 8, 12, 18, and 24 months of corrected age) when the child ' s health and growth, eating and feeding, neurodevelopment, and parental well-being are evaluated. ePIPARI consists of several widely used, standardized questionnaires, in addition to questions typically presented to parents in clinical follow-up visits. It also provides video guidance and written information about age-appropriate neurodevelopment for the parents.Parents of children born before 34 weeks of gestation during years 2019-2022 are being invited to participate in the ePIPARI study, in which web-based follow-up with ePIPARI is compared to clinical follow-up. In addition, the parents of children born before 32 weeks of gestation, who reached the corrected age of two years during 2019-2021 were invited to participate for the assessment point of 24 months of ePIPARI. The parents are asked to fill in the online questionnaires two weeks prior to each clinical follow-up visit.
Discussion The web-based tool, ePIPARI, was developed to acquire a sensitive and specific tool to detect infants and parents in need of further support and clinical interventions. This tool could allow individualized adjustments of the frequency and content of the clinical visits.